Dasatinib and FLAG-IDA Is an Effective Therapy for Initial Myeloid Blast Crisis but Involves a High Risk of Opportunistic Infections - Labrador, Jorge; Hermida, Gerardo J.; Alvarez, Rodolfo; Anso, Victor; de Vicente, Pilar; Goñi, Mercedes; Gonzalez-Lopez, Tomas Jose (Case Reports in Hematology, 2020)
Blast crisis (BC) continues to be the major challenge in the treatment of chronic myeloid leukemia. Best results have been observed in a few patients who were successfully transplanted after returning to chronic phase. Recent studies focus on the combination of chemotherapy with imatinib, but results remain unsatisfactory. Since dasatinib induces deeper and faster responses, a reasonable strategy might be to combine it with chemotherapy, taking into account the alterations in T-cell response induced by dasatinib. However, there are no published studies or case reports supporting the use of dasatinib as first line treatment for initial myeloid BC, and very little is known about infectious complications associated with this drug. Based on this, we present the case of a patient diagnosed with an initial nonlymphoid phenotype BC, who achieved molecular response (MR4.5) with dasatinib and FLAG-IDA, but he suffered a pulmonary aspergillosis, CMV infection, and a CMV reactivation, prior to an allogeneic hematopoietic stem cell transplantation (HSCT). In conclusion, dasatinib and FLAG-IDA is an effective therapy for initial BC. However, a warning call is needed owing to the high risk of opportunistic infections, such as CMV.